Sergeant Rutledge [videorecording (DVD)] - Ford, John, 1894-1973; Bellah, James Warner, 1899-1976; Goldbeck, Willis; Goldbeck, Willis; Hunter, Jeffrey, 1926-1969; Towers, Constance; Burke, Billie, 1885-1970; Strode, Woody; Hernandez, Juano; Bouchey, Willis; Young, Carleton, 1907-1971; Pratt, Judson, 1916-2002 (John Ford film collection., 2006)
An African-American "buffalo soldier" is accused of rape and murder, but is successfully defended by a white officer during his trial in 1881.